Pengembangan Media Pembelajaran Video Animasi Berbasis Model Problem Based Learning Pada Pembelajaran IPAS di Kelas IV Sekolah Dasar - Rani Chairunnisha; Arwin Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
This research aims to develop an animated learning video media using an app called Canva for the Science and Social Studies (IPAS) subject in 4th-grade elementary students. The research was motivated by a lack of variety, technology-based media, which leads to students losing focus, becoming easily bored, and struggling to solve problems. The development followed the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, questionnaires, expert assessments, and instruments of validity, practicality, and effectiveness. Product validated by experts in the field of contet, language, and media, achieving a validity score of 88.77% (highly valid). Trials were conducted in several elementary schools in Padang. Practicality results showed teacher responses of 95% and student responses of 90.18% (highly practical). Effectiveness tests showed an average learning outcome of 78% for Topic A and 76% for Topic B (effective). Thus, the Canva-based animated video media developed using the PBL approach is considered valid, practical, and effective for supporting IPAS learning.